Klimaszewskityrus nom. nov., a new replacement name for Klimaszewskia Yin & Zhang, 2021 - Yin, Zi-Wei; Zhang, Wen-Xuan (Zootaxa, 2021)
The genus Klimaszewskia Yin & Zhang of the pselaphine tribe Tyrini was recently established to include a single species, viz., K. punctata Yin & Zhang, from Indonesia (Yin & Zhang 2021). However, the generic name was preoccupied by Klimaszewskia Szelegiewicz, 1979 (Hemiptera, Aphididae). In accordance with the International Code of Zoological Nomenclature (ICZN 1999: Article 60.3), a new replacement is here proposed.